Four Levers of Control in the Implementation of Supply Chain Management in Government Institutions - Agus Bandiyono; Arief Al Fikri (International Journal of Supply Chain Management, 2020)
Abstract- The current state of the government’s Supply Chain Management (SCM) is fraught with malpractices which include lack of good governance, fair, equitable, transparent, competitive and cost-effective procurement process. The management challenges for the Central Jakarta DJP Regional Office are not only performance targets that have not been achieved over the past three years but are coupled with an increase in revenue targets each year that can affect employee motivation at work. With the decline in performance and supply chain management issues identified through the pre-research survey, the authors intend to research the supply chain management system in the Central Jakarta Regional Tax Office using the model approach four levers of control. The application of boundary systems in the form of business conduct boundaries and strategic boundaries is quite reliable. The implementation of the interactive control system is realized by the creation of a discussion room by top management and the establishment of good internal communication between employees in the Central Jakarta DJP Regional Office. Application of diagnostic control system in the form of a planning system with planning that refers to the 2015-2019 Directorate General of Tax Strategic Plan, implementation of budgeting in the form of performance-based budgeting.  Generally, SCM performance in the various surveyed government, although it became evident that the departments experience obstacles during the implementation of SCM processes and procedures. Furthermore, procurement planning is inadequate and needs improvement when the departments procure goods, services or works. Procurement execution was also found wanting, especially with regards to procurement governance.